Urban geography and protest mobilization in Africa. (July 2016) - Fox, Sean; Bell, Andrew
Abstract: Urbanization has long been seen by scholars and policymakers as a disruptive process that can contribute to social and political unrest, yet there is little cross-national quantitative empirical research on the topic. In this paper we provide a comprehensive analysis of the links between urban geography and the incidence of protests (i.e. demonstrations, riots and strikes) in African countries since 1990. In contrast to previous studies, we are careful to distinguish between urban population scale effects, urban population ratio effects, population rate-of-change effects and urban population distribution effects. We also provide an explicit test of the long-standing hypothesis that 'over-urbanization' increases the risk of civil unrest. Employing multilevel negative binomial models that control for key political and economic variables we find that urban population size and the number of large cities in a country are both positively and significantly associated protest incidence. By contrast, we find that a country's level of urbanization is negatively associated with protest incidence and reject the over-urbanization hypothesis: higher levels of urbanization are associated with less frequent protests at all income levels. We find no evidence that the pace of urban population growth or urban primacy significantly influence protest mobilization. In sum, our results provide a nuanced picture of the relationship between urban geography and protest incidence that challenges conventional wisdom and contemporary hyperbole about the dangers of 'rapid urbanization' in Africa in particular, and developing countries more generally.